Pengaruh Layanan Bimbingan Klasikal Symbolic Modelling Terhadap Motivasi Belajar Peserta Didik Sekolah Dasar - Kurnia Rahmawati; Tri Suyati; Farikha Wahyu Lestari (Universitas Sebelas Maret, 2021)
The purpose of this research is to find out the effect of classical guidance with Symbolic Modelling technique to the Students’ of Kebonagung Elementary School learning motivation. The approach of this research is quantitative. The type of this research is pretestposttest control design group. The instrument of this research is questioner that consists of 21 items. Test of normality are used Kolmogorov-Smirnov Test and Shapiro-Wilk Test. Test of Homogeneity is used Levene Test. Test of difference is used Paired Sample t Test. The result of this research is experiments group’s learning motivation improved from the average on 48,103, including middle category (C) to the average on 61,068, including high category (B) and the correlation on Paired Sample t Test on 0,946, signification on 0,000 which smaller than 0,05 (0,000 < 0,05). So, it is an effect of classical guidance with Symbolic Modelling technique to the Students’ of Kebonagung Elementary School learning motivation. The effect is nearly perfect and significant.